16S rRNA and Omp31 Gene Based Molecular Characterization of Field Strains of B. melitensis from Aborted Foetus of Goats in India - Ajay Singh; Vivek Kumar Gupta; Amit Kumar; Vikas Kumar Singh; Shivasharanappa Nayakwadi (The Scientific World Journal)
Brucellosis is a reemerging infectious zoonotic disease of worldwide importance. In human, it is mainly caused by Brucella melitensis, a natural pathogen for goats. In India, a large number of goats are reared in semi-intensive to intensive system within the close vicinity of human being. At present, there is no vaccination and control strategy for caprine brucellosis in the country. Thus, to formulate an effective control strategy, the status of etiological agent is essential. To cope up with these, the present study was conducted to isolate and identify the prevalent Brucella species in caprine brucellosis in India. The 30 samples (fetal membrane, fetal stomach content and vaginal swabs) collected throughout India from the aborted fetus of goats revealed the isolation of 05 isolates all belonging to Brucella melitensis biovars 3. All the isolates produced amplification products of 1412 and 720 bp in polymerase chain reaction with genus and species specific 16S rRNA and omp31 gene based primers, respectively. Moreover, the amplification of omp31 gene in all the isolates confirmed the presence of immuno dominant outer membrane protein (31 kDa omp) in all the field isolates of B. melitensis in aborted foetus of goats in India. These findings can support the development of omp31 based specific serodiagnostic test as well as vaccine for the control of caprine brucellosis in India.